RESEARCH OF GEOLOGIC STRUCTURE OF TERRITORIES OF HYDROTECHNICAL SYSTEMS ALLOCATION BY MEANS OF GEOPHYSICAL METHODS (USING "SENZHE" HPP AS AN EXAMPLE, EQUATORIAL GUINEA) - Vyzhva, S.; Onyshchuk, V.; Ivanchenko, K.; Onyshchuk, I.; Reva, M.; Deineko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to peculiarities of application of electrical exploration method for engineering-geophysical and geophysical investigations to ensure the construction of hydropower plants in tropical conditions on the territory of Equatorial Guinea. Also the article discusses informativeness of proactive geophysical studies, in result of which block structure of geological section of the area was found. Comprehensive analysis of the vertical section, resistivity maps and drilling data showed that increased resistance zones are controlled by monolithic rocks of dyke complex and low-resistance zones are associated with areas of varying degrees of fractured crystalline rocks. Maps of the apparent electrical resistance at different set spans allowed to unravel the three-dimensional structure of investigated area in an electric field and provided valuable information for drawing up its conditioning geological basis. The basis of the geological section consists of Precambrian crystalline rocks that vary considerably in resistivity – from 780 to 50,000 Ohm × m, and the values of the speed of propagation of refracted waves are from 2.7 km/s to 7.0 km/sec. A wide range of geophysical characteristics of crystalline basement rocks indicates a significant change of fracture intensity and rock decay that should be considered when drawing up the master plan of HPP facilities allocation.
Keywords: engineering-geophysical investigations; crystalline rocks; electrical resistivity; vertical electrical sounding